Cultural imageability on urban identity: a systematic literature review - Patria @ Ahmad Patria, Abdullah Hasif; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati (RSIS International, 2024)
Purpose - The relationship between cultural imageability and urban identity is examined in this systematic literature review based on several themes, highlighting the influence of cultural factors on how urban places are perceived and represented. This systematic literature review aims to provide insights for researchers in the fields of urban studies and landscape architecture, as well as architecture, in understanding the various ways that cultural imageability influences the development of urban identity. Methodology - In order to thoroughly synthesize research, the author used a systematic literature review (SLR) technique. A total of 27 articles were found in the first step, and a final sample of 10 research studies was synthesized. Findings – The findings showcased the impact of culturally integrated elements and spaces on how urban areas are seen and portrayed, emphasizing the city's ability to elicit feelings and connections that are ingrained with its residents' cultural identities. Limitations – The author encounters obstacles regarding the current protocols for conducting SLR that provide little direction in the context of the built environment. The optimal decisions regarding which steps to take in the SLR process often remain unclear, which may have an impact on the comprehensiveness of this systematic literature review. Originality - This SLR addresses a subject that is becoming an important topic in urban studies and environmental psychology by concentrating on the relationship between cultural imageability and urban identity using SLR as the methodology.